Effects of Feeding of Two Potentially Probiotic Preparations from Lactic Acid Bacteria on the Performance and Faecal Microflora of Broiler Chickens - Paula Fajardo; Lorenzo Pastrana; Jesús Méndez; Isabel Rodríguez; Clara Fuciños; Nelson P. Guerra (The Scientific World Journal)
The aim of this study was to evaluate the potential of two probiotic preparations, containing live lactic acid bacteria (Lactococcus lactis CECT 539 and Lactobacillus casei CECT 4043) and their products of fermentation (organic acids and bacteriocins), as a replacement for antibiotics in stimulating health and growth of broiler chickens. The effects of the supplementation of both preparations (with proven probiotic effect in weaned piglets) and an antibiotic (avilamycin) on body weight gain (BWG), feed intake (FI), feed consumption efficiency (FCE), relative intestinal weight, and intestinal microbiota counts were studied in 1-day posthatch chickens. The experiments were conducted with medium-growth Sasso X44 chickens housed in cages and with nutritional stressed Ross 308 broiler distributed in pens. Consumption of the different diets did not affect significantly the final coliform counts in Sasso X44 chickens. However, counts of lactic acid bacteria and mesophilic microorganisms were higher in the animals receiving the two probiotic preparations (P<0.05). In the second experiment, although no differences in BWG were observed between treatments, Ross 308 broilers receiving the probiotic Lactobacillus preparation exhibited the lowest FCE values and were considered the most efficient at converting feed into live weight.